2020
DOI: 10.4317/medoral.23719
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors related to oral candidiasis in patients with primary Sjögren’s syndrome

Abstract: Background Candidiasis is the most frequent mycotic infection of the oral cavity. The aim of this study was to investigate the presence of clinical oral candidiasis and Candida albicans yeast in a population diagnosed of primary Sjögren’s syndrome (pSS) and to study the possible factors associated with this infection. Material and Methods An observational cross-sectional study was conducted in 61 pSS patients (60 women, 1 man, mean age 57.64±13.52) where patient based i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…), autoimmune diseases (Sjögren syndrome, etc. ), HIV, and primary immunodeficiencies [ 57 , 58 , 59 ].…”
Section: Clinical Manifestations Of Candidiasismentioning
confidence: 99%
“…), autoimmune diseases (Sjögren syndrome, etc. ), HIV, and primary immunodeficiencies [ 57 , 58 , 59 ].…”
Section: Clinical Manifestations Of Candidiasismentioning
confidence: 99%
“…Additionally, studies have shown that most patients with COVID-19 have one or more systemic (e.g., use of broad-spectrum antibiotics, use of corticosteroids, immunosuppression) or local (e.g., use of dental prostheses, reduced salivary flow due to use of medication) risk factors that favor Candida proliferation. 23 25 …”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the only other study to measure both the unstimulated and stimulated salivary flow rate in SS patients was that of Serrano et al . [2020] ( 19 ). Their analysis showed that 60.7% of SS patients had a decreased UWSFR.…”
Section: Discussionmentioning
confidence: 99%